2020
DOI: 10.3390/ijerph17030978
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Cigarettes in Smoke-Free Spaces by Smokers: Results from the 2014–2015 Population Assessment on Tobacco and Health Study

Abstract: Background: Smoke-free air policies exist to protect users and nonusers from exposure to tobacco smoke. Although electronic nicotine delivery systems (ENDS) may expose passerby to nicotine and particulate matter, few US states regulate indoor use of ENDS. The purpose of this study was to investigate reported rationales for ENDS use and reported ENDS use in public smoke-free places by dual cigarette/ENDS users. Methods: A population of ENDS/cigarette co-users (n = 2051) was drawn from Wave 2 of the Population A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Overall, reported e-cigarette use to cut down on cigarette smoking (OR 2.38, 95% CI 1.86 to 3.05), as an alternative to quitting (OR 1.71, 95% CI 1.37 to 2.13), or because of belief that e-cigarettes help people to quit cigarette smoking (OR 1.52, 95% CI 1.20 to 1.92) were significantly associated with increased odds of vaping in smoke-free places. 57 In our present study, however, it was not clear whether the high prevalence of not vaping in smoke-free spaces was because of existing smoke-free regulations and/or enforcement of any such regulations or whether it was based solely on vapers' own judgement. Further research is needed to monitor patterns of e-cigarette use in smoke-free spaces and the perceptions of non-vapers who share these spaces.…”
Section: E-cigarette Use Behaviourcontrasting
confidence: 61%
See 1 more Smart Citation
“…Overall, reported e-cigarette use to cut down on cigarette smoking (OR 2.38, 95% CI 1.86 to 3.05), as an alternative to quitting (OR 1.71, 95% CI 1.37 to 2.13), or because of belief that e-cigarettes help people to quit cigarette smoking (OR 1.52, 95% CI 1.20 to 1.92) were significantly associated with increased odds of vaping in smoke-free places. 57 In our present study, however, it was not clear whether the high prevalence of not vaping in smoke-free spaces was because of existing smoke-free regulations and/or enforcement of any such regulations or whether it was based solely on vapers' own judgement. Further research is needed to monitor patterns of e-cigarette use in smoke-free spaces and the perceptions of non-vapers who share these spaces.…”
Section: E-cigarette Use Behaviourcontrasting
confidence: 61%
“…Non-smokers and younger participants (18-20 years) were more likely to report not vaping in smoke-free spaces than cigarette smokers and older participants, respectively. Using data drawn from Wave 2 of the Population Assessment of Tobacco and Health (PATH) dataset (2014-2015), 57 Dunbar and colleagues found that 54.0% of respondents aged 18-24 years who vaped and smoked cigarettes (ie, dual users) reported vaping in smoke-free spaces. Overall, reported e-cigarette use to cut down on cigarette smoking (OR 2.38, 95% CI 1.86 to 3.05), as an alternative to quitting (OR 1.71, 95% CI 1.37 to 2.13), or because of belief that e-cigarettes help people to quit cigarette smoking (OR 1.52, 95% CI 1.20 to 1.92) were significantly associated with increased odds of vaping in smoke-free places.…”
Section: E-cigarette Use Behaviourmentioning
confidence: 99%
“…In the wave 1 PATH Study survey in 2013-2014, 80% of those who had used an e-cigarette indicated that a reason for use was that they could vape at times when, or in places where, smoking cigarettes was forbidden, 20 and such use 17 is common. 21 Such a secondary role for e-cigarettes may change with the more efficient e-cigarette nicotine delivery systems 17 that became popular in the United States after 2017. 22,23 The PATH Study has numerous strengths.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of policies targeting cigarettes may be altered by the availability of NVPs. While NVPs may blunt the impact of some cigarette-oriented policies (e.g., use of NVPs in areas that are smoke-free, but not vape-free) [ 105 ], NVPs may instead enhance policy impacts, because smokers may substitute NVPs for cigarettes in response to stricter cigarette-oriented policies. Indeed, demand studies [ 106 , 107 , 108 , 109 ] indicate that NVPs are a substitute for cigarettes, and cessation studies [ 17 , 18 , 19 , 20 , 110 , 111 ] indicate that NVPs are often used by those who have had limited success with traditional cessation treatments.…”
Section: Discussionmentioning
confidence: 99%